Minimization of Surgical Site Infections in Patients With Delayed Sternal Closure After Pediatric Cardiac Surgery. Issue 4 (July 2019) - Yabrodi, Mouhammad; Hermann, Jeremy L.; Brown, John W.; Rodefeld, Mark D.; Turrentine, Mark W.; Mastropietro, Christopher W.
Background: Delayed sternal closure (DSC) following pediatric cardiac surgery is commonly implemented at many centers. Infectious complications occur in 18.7% of these patients based on recent multicenter data. We aimed to describe our experience with DSC, hypothesizing that our practices surrounding the implementation and maintenance of the open sternum during DSC minimize the risk of infectious complications. Methods: We reviewed patients less than 365 days who underwent DSC between 2012 and 2016 at our institution. Infectious complications as defined by the Society of Thoracic Surgeons Congenital Heart Surgery Database were recorded. Patients with and without infectious complications were compared using Wilcoxon rank sum tests or Fisher exact tests as appropriate. Results: We identified 165 patients less than 365 days old who underwent DSC, 135 (82%) of whom had their skin closed over their open sternum. Median duration of open sternum was 3 days (range: 1-32 days). Infectious complications occurred in 15 (9.1%) patients—13 developed clinical sepsis with positive blood cultures, one patient developed ventilator-associated pneumonia, and one patient developed wound infection (0.6%). No cases of mediastinitis occurred. No statistical differences in characteristics between patients with and without infectious complications could be identified. Conclusion: Infectious complications after DSC at our institution were notably less than reported in recent literature, primarily due to minimization of surgical site infections. Practices described in the article, including closing skin over the open sternum whenever possible, could potentially aid other institutions aiming to reduce infectious complications associated with DSC.